Biosynthesis and characterization of silver nanoparticles using ginger spent and their antibacterial activity - Ganesan, Sinthia; Mehalingam, Palanichamy; Selvam, Govindan Sadasivam (Current Botany, 2021)
Ginger spent is the byproduct of spice industries that remove the essential oils of ginger (Zingiber officinale) for food industry and medicinal purposes. Ginger is a well known spice used often for seasoning in Indian cuisine. The de-oiled ginger has no specific use mostly goes to waste. Hence, we utilized this industrial waste product in the efficient synthesis of silver nanoparticles with the aid of UV irradiation from a solution of 1mM silver nitrate and spent extract in the ratio 9:1. Immediate colour change from pale yellow to dark brown was noted indicating the rapid synthesis of silver nanoparticles. These nanoparticles were centrifuged, dried and well characterized. UV Vis Spectroscopy, XRD analysis, Zeta potential and SEM analysis was carried out. It was commendable that the size of the nanoparticles fell well within the upper limit of 100nm. Agar well diffusion method was used to screen the antimicrobial activity of the well characterized silver nanoparticles. They were tested against seven pathogenic strains of three gram negative bacteria (Escherichia coli, Klebsiella pneumonia and Pseudomonas aeruginosa) three gram positive bacteria(Bacillus subtilis, Staphylococcus aureus and Streptococcus faecalis) and a fungus (Candida albicans). It was seen that the zone of inhibition(ZOI) in well plate method increased on increasing the concentration of silver nanoparticles. Further studies could lead to the application of these silver nanoparticles in medicine.